Present to Future - Larry Bowne; Patrick Rhodes (Oz, 2006)
This articles features a transcript of a conversation between Larry Bowne and Patrick Rhodes about humanitarian design and Rhodes’ efforts at disaster relief in New Orleans in the wake of Hurricane Karina.